Obstacles to the Application of Administrative Process Engineering in Gaza Universities from the Faculty Members' Perspective - Mahmoud A.R. Assaf (University of Science and Technology, Yemen, 2017)
The study aimed to identify the faculty members' levels of assessment at Palestinian universities of the obstacles to the application of engineering of administrative processes ; and to find out whether there were statistically significant differences at the level of significance (α≤0.05) between the mean scores of assessment attributable to the variables: (college, academic rank, years of service). To achieve this, the researcher followed the descriptive method by using a questionnaire consisting of 36 items distributed into 4 areas: (technical, human, financial, administrative). The sample consisted of (95) faculty members from two universities (Al-Azhar and Islamia). The study revealed that the total degree of the respondents' assessment of the obstacles to the application of engineering of administrative processes was (73.4%). The order of obstacles was as follows: i) financial, ii) human, iii) administrative and iv) technical obstacles. Further, there were no statistically significant differences at the level of significance (α≤0.05) between the mean scores of respondents' assessment of the obstacles to the application of this method at the Palestinian universities that were attributed to these variables: (college, academic rank, years of service).The study recommended the need for allocating of adequate financial budgets, and the creation of a special unit in each university to be responsible for providing training on the concepts of reengineering administrative processes and linking them to quality and continuous improvement. Keywords: Administrative process engineering, Gaza governorates , Faculty members.